2002
DOI: 10.1203/00006450-200202000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Formation of Free Radicals Plays a Minor Role in Hypoxic Cell Death in Human NT2-N Neurons

Abstract: Free radicals are suggested to play an important role in hypoxic-ischemic neuronal death. However, the importance in human disease is not known. Furthermore, whether posthypoxic free radical formation mainly occurs in endothelium and neutrophils, or whether neuronal production is important, is not finally determined. To study this we differentiated human Ntera2 teratocarcinoma cells into postmitotic NT2-N neurons and exposed them to free radicals, hypoxia, or oxygen and glucose deprivation. These cells are dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
1
6
1
Order By: Relevance
“…In the present study, acidosis (during both ischemia and reoxygenation) increased the formation of isoprostanes by 50%. We have previously found that neuronal free radical formation during and after OGD (with neutral medium) plays a minor role in this model (Almaas et al 2002); the current study confirms these findings as there were no significant difference in the levels of isoprostanes between oxygen-and glucose-deprived neurones with neutral medium compared with normoxic cells with neutral medium. The effects of antioxidants were not tested in the current experiments, so whether the acidosis-induced 50% enhancement of free radical formation is an important cause of the deleterious effect of acidosis during reoxygenation has not been settled.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, acidosis (during both ischemia and reoxygenation) increased the formation of isoprostanes by 50%. We have previously found that neuronal free radical formation during and after OGD (with neutral medium) plays a minor role in this model (Almaas et al 2002); the current study confirms these findings as there were no significant difference in the levels of isoprostanes between oxygen-and glucose-deprived neurones with neutral medium compared with normoxic cells with neutral medium. The effects of antioxidants were not tested in the current experiments, so whether the acidosis-induced 50% enhancement of free radical formation is an important cause of the deleterious effect of acidosis during reoxygenation has not been settled.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, acidosis (during both ischemia and reoxygenation) increased the formation of isoprostanes by 50%. We have previously found that neuronal free radical formation during and after OGD (with neutral medium) plays a minor role in this model (Almaas et al . 2002); the current study confirms these findings as there were no significant difference in the levels of isoprostanes between oxygen‐ and glucose‐deprived neurones with neutral medium compared with normoxic cells with neutral medium.…”
Section: Discussionmentioning
confidence: 69%
“…Acidosis causes a 50% increase in free radical formation in the current model (1). However, as we have previously found a rather limited role for free radicals in hypoxic cell death of NT2-N neurons, this may not sufficiently explain the deleterious effect of acidosis during reoxygenation (3).…”
contrasting
confidence: 51%
“…A possible aggravating effect of acidosis during reoxygenation could be through an increase in free radical formation (1,23), but we have not found oxygen radicals to be important mediators of cell death in our model (3). Another possible detrimental effect of acidosis during reoxygenation could be through a negative effect on mitochondrial function.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation